Fiqh of the Future Prophetic Messages, Question of Importance and Method: فقه الإخبارات النبوية المستقبلية، سؤال الأهمية والمنهج - Mohamed Sedra, Saad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
وجهتنا السنة النبوية في كثير من نصوصها إلى ضرورة الاهتمام بالمستقبل، ويبقى من الواجب علينا فقه هذه الإخبارات النبوية المستقبلية، والعمل بمقتضاها، وهذا ما سعى هذا البحث لإظهار أهميته وبيان منهجه، من خلال الجواب على سؤالين مهمين؛ الأول: يتعلق بمدى أهمية هذا النوع من الفقه الموضوعي للأحاديث المتعلقة بالمستقبل. والثاني: يتعلق بالمنهج المؤطر لعملية فهم وتنزيل هذه الأحاديث على واقع ومستقبل الأمة المسلمة. وقد اعتمدت في هذا البحث منهجا تحليليا وتركيبيا قصد بيان المقصد النبوي من هذه الإخبارات، وتوضيح السبيل الأمثل لفهمها. إن غاية هذا الأمر هو بناء تصورات واضحة المعالم لما سيواجهه المسلمون في المستقبل، بغية تحفيزهم واعانتهم على حسن الاستعداد المسبق له، حتى تكون الأمة في مجموعها مستعدة لخوض غمار المستقبل بأفضل شكل ممكن. الكلمات المفتاحية: فقه، المستقبل، المنهج Abstract The Sunnah of the Prophet has guided us in many of its texts to the importance of looking to the future. It remains for us the duty to better understand these messages, and to make them practicable. This is then the purpose of this research, to clarify and present its methodology where two important questions are asked: 1: Concerns the importance of this type of Fiqh? 2: Concerning the method that frames the operation of understanding these Hadiths of the Prophet on the future of the Islamic community. In this research, I have taken an analytical and compositional approach to explain the prophetic purpose of these stories and how best to understand them. Thus, the purpose of this topic is to build clear visions on the obstacles that the Muslims will face in the future, in order to encourage and help them to better prepare themselves for what will face them, so the Muslim community will be prepared to better introduce itself in the future. Keywords: Fiqh, Future, Method.